Optimisation of enzymatic hydrolysis of monkfish heads for preparing protein hydrolysates as animal feed ingredient - Greyling, Nanette (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.